2011
DOI: 10.1007/s12221-011-0816-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of acid cellulose enzyme concentration to reduce pilling of bamboo fabric: An objective assessment approach

Abstract: Enzymes are being extensively used in industry as they are environmentally friendly. They show a variety of advantages over chemicals, like their specificity, high efficiency and eco-friendliness. Nowadays different kinds of cellulase enzyme mixtures are commercially formulated for the finishing of cellulosic fabrics. This study investigated the effect of acid cellulase treatment on bamboo knitted-fabric to reduce pill. It has been observed that specific range of concentration only can effectively reduce pills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…White part of this binary image representing the pill located on the fabric was counted in terms of "ON" pixel. Parameters related to pilling evaluation like number, area, and rating were also obtained [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…White part of this binary image representing the pill located on the fabric was counted in terms of "ON" pixel. Parameters related to pilling evaluation like number, area, and rating were also obtained [29].…”
Section: Methodsmentioning
confidence: 99%
“…Objective measurement of pilling evaluation has been topic of many research publications. Laser triangulation method [21], image synthesis based on the Karhunen-Loeve transform [22], digital image analysis [23], two-dimensional Gaussian fit theory to train pill template while using actual pill images for template matching [24], frequency domain analysis algorithm [25], light projection image analysis [26], noncontact three-dimensional measurement system using slit laser beam projector and CCD camera [27], wavelet reconstruction scheme using discrete wavelet transform [28], and fast Fourier transformation technique [13,29] are important to mention in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…In practical applications, BP model has disadvantages, which include slow convergence rate and local minimum value. 22 Using genetic algorithm (GA) to optimize the initial weight and threshold of BP model can improve the training speed of neural network and overcome local minimum. Zhang et al 23 used GA to detect and classify color-textured fabrics defects, and found that it was more feasible and applicable.…”
Section: Introductionmentioning
confidence: 99%
“…However, pilling of knitted cellulose fibers products is an undesirable phenomenon during wearing and laundering that affects the handle and appearance and greatly shortens the service life of the products [7][8][9][10]. Pilling of knitted cellulose fabrics is a complex and dynamic process, in which the loose fibers separate from the yarn due to mechanical stresses such as rubbing, external pressure and fiber-fiber friction, and then intertwine with each other and appear on the surface of the fabric, resulting in pilling phenomenon [4,[11][12][13]. In the blended fabric of cellulose and chemical fibers, the chemical fiber plays the role of an anchoring fiber because of its high strength, which makes the pilling of cellulose fibers less easy to fall off and aggravates the pilling period [14].…”
Section: Introductionmentioning
confidence: 99%
“…What is more, some outfield induced methods have been developed to modify fabrics to achieve ecological sustainability [4]. For example, Kahandual [12] proved that cellulase could improve the pilling performance of bamboo fibers. Noreen [23] used aspergillus niger to improve the pilling resistance of polyester/cotton blended fabric.…”
Section: Introductionmentioning
confidence: 99%